Body Ignorance and Toughness Culture: Injury Issues among Elite Indonesian Athletes - Rahayuni, Kurniati (KnE Life Sciences, 2021)
Elite sport is a demanding career and injuries are common among elite athletes. However, empirical attempts to understand it in the Indonesian context through a sport psychology perspective has been rare. In this qualitative research about Indonesian elite athlete psychological demands, 37 elite athletes and 9 sport practitioners were interviewed through semi-structured interview and photographic elicitation interview (PEI) and data were analysed using a reflexive thematic analysis. The results showed that athletes realised that their elite athletic career is ephemeral and will come to retirement; during that short time, they moved along in a continuum of caring and exploiting their body. Two distinct sub-themes about injury built from the analysis were: (i) Exploiting the body versus caring the body, which reflects the dynamic stance of athletes in treating their body and its influential factors. (ii) The social environment around athletes that promotes ignorance versus support, which describes the cultural and social nuances of injury. Implications and invitations for future research through a multidisciplinary approach of health and sport sciences is also discussed. Keywords: injury, elite athlete, Indonesia